Tax Planning, Earning Management, dan Corporate Governance Terhadap Transfer Pricing: Analisis Moderasi (Studi Empiris pada Perusahaan Sektor Consumer non cyclical di BEI 2019-2023) - Niken Handayani, Rukmining Tias; Haryati, Tantina (Journal of Business and Economics Research (JBE), 2025)
Transfer pricing practices in multinational companies are a crucial issue in international taxation, especially in the context of Indonesia. This study aims to analyze the influence of tax planning, earnings management, and corporate governance on transfer pricing practices, as well as the role of profitability as a moderating variable. Secondary data in the form of annual reports from multinational companies in the non-cyclical consumer sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023 from 10 sample companies (selected using purposive sampling) were analyzed using Structural Equation Modeling (SEM) with SMART PLS. The results indicate that tax planning (coefficient = -0.011, p = 0.971) and earnings management (coefficient = -0.053, p = 0.619) have a negative and insignificant effect on transfer pricing. Conversely, corporate governance (coefficient = 0.697, p = 0.000) has a positive and significant effect on transfer pricing. Profitability as a moderator is not significant in influencing the relationship between the three independent variables and transfer pricing. The research model has an R2 value of 0.723. This study provides empirical evidence regarding the determinants of transfer pricing in Indonesia and the implications of profitability in this dynamic.